Fear [compact disc, unabridged] : Trump in the White House - Woodward, Bob, 1943- (Audioworks, Simon & Schuster Audio, 2018)
Draws on interviews with firsthand sources, meeting notes, personal diaries, and other documents to depict life in the Trump White House, focusing on Trump's decision-making process for foreign and domestic policies.